Comrades in Arms : Military Masculinities in East German Culture - Smith, Tom 1987- (Berghahn Books, 2020)
Without question, the East German National People’s Army was a profoundly masculine institution, not simply in terms of its overwhelmingly male makeup but in the traditional ideals of stoicism, sacrifice, and physical courage that it sought to exemplify. Nonetheless, as this innovative study of the army’s cultural representations demonstrates, depictions of the military in East German film and literature were far more nuanced and ambivalent. Departing from past studies that have found in such depictions an unchanging, idealized masculinity, Representing the East German Soldier shows how cultural works both before and after reunification portrayed violence, physical vulnerability, military theatricality, and the powerful emotions and desires of conscripts to explore a surprisingly wide range of complex and contested masculinities